KAJIAN INTERTEKSTUAL SYAIR SIAK SRI INDRAPURA DAR AL-SALAM AL-QIYAM DENGAN NASKAH DRAMA PENGABSAHAN RAJA KECIL (ANAK MAYAT) - Rani Hidayati; Elmustian Elmustian; Mangatur Sinaga (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This thesis is titled "Intertekstual Study of Syair Siak Sri SyaiIndrapura Dar Al-Salam Al-Qiyam with Drama script of Pengabsahan Raja Kecil (Anak Mayat)". This study aims as follows. The purpose of this study is to describe the relationship and the differences in the building blocks of the Syair Siak Indrapura manuscript Dar Al-Salam Al-Qiyam and the Theater Manuscript Pengabsahan Raja Kecil (Anak Mayat) which are limited to aspects of character, plot and setting. The research method used is the intertext method. Intertext method is a method that links other texts in a study. As the essence of a text in which there is another text. The theory used in this study is intertextual, structuralism, poetry, drama script. This research is a descriptive qualitative study that describes and describes the results of the study. The nature of the hypogram can be classified into three types, namely negation, affirmation, and innovation. The results show that (1) the similarities and differences in the constructing elements of the two manuscripts and (2) the intertextual relationship between drama scripts Legitimate the Little King (Corpses) and Poetry Siak Sri Indrapura Dar Al-Salam Al-Qiyam in the form of negation, affirmation, and Innovation.Key Words: intertextual, drama script, Syair Siak Sri Indrapura, drama script Anak Mayat.